Trace compounds in the urban water cycle in the Freiberg region, Germany - Dibyanshu,; Kern, Marco; Scheytt, Traugott (Frontiers in Water, 2024)
Urban water contamination has become a pressing concern due to the surge in urbanization, industrialization, and population growth, resulting in increased pollution levels and the introduction of emerging contaminants (ECs) into the environment. The widespread use of pharmaceuticals (PhACs), driven by medical advancements and economic progress, has led to their presence in aquatic systems, posing risks to both ecosystems and human health. These compounds are released into the environment via effluent of wastewater treatment plants (WWTPs) as they are inefficient in totally removing PhACs. This study focused on PhACs in wastewater, surface water and groundwater of a small city like Freiberg region in Germany. Samples were collected along Münzbach's path, encompassing hospital discharges and WWTP. Analysis for the measurement of PhACs was conducted via Ultra-high-performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS). Results revealed that about 46 out of 54 analyzed PhACs were detected across matrices, with positive findings of 46 substances in wastewater, 37 in surface water, and 19 in groundwater. Among 54 analyzed PhACs, six of the active pharmaceutical ingredients (APIs) like atenolol (ATL), carbamazepine (CBZ), caffeine (CAF), diclofenac (DCF), metformin (MET), and sulfamethoxazole (SMX) were focused in this study. Five of the six APIs were present in all matrices, with MET and CAF widely distributed in an aqueous system. CBZ and DCF were found in wastewater and surface water, ATL was scarce in surface water, while SMX was absent in groundwater. It was observed that PhAC concentration was reduced from wastewater to groundwater, with the highest levels near the WWTP, decreasing as effluents flowed through surface water Münzbach and Freiberger Mulde. It was also observed that the groundwater near the surface water shows the presence of APIs mainly due to the hyporheic zone connecting the surface water and groundwater. Overall, PhAC compounds reflect the city population and their age, the water cycle, and the hydrochemical processes of the compounds themselves.